2017
DOI: 10.1161/strokeaha.117.017877
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Sex Differences in Magnetic Resonance Imaging-Depicted Carotid Intraplaque Hemorrhage

Abstract: Background and Purpose Stroke rates are higher in males compared to females in the fourth through seventh decades of life, and higher rates may result from differences in carotid intraplaque hemorrhage (IPH), an unstable atherosclerotic plaque component. We report age-specific sex differences in the presence of MRI depicted carotid IPH. Methods Patients (n=1115) underwent MRI for carotid IPH between 2005 and 2014. Low-grade carotid stenosis patients (n=906) without prior endarterectomy were eligible for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 46 publications
(59 reference statements)
3
16
0
Order By: Relevance
“…Together, these findings suggest that younger patients may be less likely to benefit from plaque imaging than those over 50 years old. These results are corroborated by Singh et al ( 12 ) who found that only 2 out of 63 patients (3.2%) with IPH were between the ages of 45–54, while 11, 14. and 36 patients were 55–64, 65–74, and >75 years, respectively. Moreover, a multitude of studies involving both symptomatic and asymptomatic patients with IPH have reported mean ages well-above 50 years of age further suggesting that IPH has an age-related dominance in patients above the age of 50 regardless of symptomatic manifestation ( 4 , 5 , 13 , 14 ).…”
Section: Discussionsupporting
confidence: 74%
“…Together, these findings suggest that younger patients may be less likely to benefit from plaque imaging than those over 50 years old. These results are corroborated by Singh et al ( 12 ) who found that only 2 out of 63 patients (3.2%) with IPH were between the ages of 45–54, while 11, 14. and 36 patients were 55–64, 65–74, and >75 years, respectively. Moreover, a multitude of studies involving both symptomatic and asymptomatic patients with IPH have reported mean ages well-above 50 years of age further suggesting that IPH has an age-related dominance in patients above the age of 50 regardless of symptomatic manifestation ( 4 , 5 , 13 , 14 ).…”
Section: Discussionsupporting
confidence: 74%
“…These sex differences in the abundances of blood coagulation proteins may have implication in the differences of intraplaque haemorrhage in men and women. Men have a greater incidence of intraplaque haemorrhage, compared to women, which is a strong predictor of future clinical events [11, 12]. Functional studies into the activity and/or interactions of antithrombin-III and FXII would provide insight into whether they provide stability, or instability, to atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…One such morphological feature that can predict the outcome and severity of plaque rupture is the amount of intraplaque haemorrhage present. In general, it has been observed that atheroma from men have more intraplaque haemorrhage [11, 12]. In our previous study, we designed a unique sampling protocol that reduced the effect of heterogeneity by analysing comparable intra-lesion biopsies from distinct regions within carotid endarterectomy samples [13].…”
Section: Introductionmentioning
confidence: 99%
“…In all patients, plaque components were evaluated using an MRI machine. 3,13,16,25 For plaque characterization, long-axis and axial images of the carotid artery were obtained with 3D gradient-echo sequences in the area with the highest degree of stenosis. Three-dimensional timeof-flight (TOF) MR angiography was acquired through both carotid bifurcations in the axial plane.…”
Section: Mr Plaque Imagingmentioning
confidence: 99%